Trophies of Victory : Public Building in Periklean Athens - Shear, Theodore Leslie jr. (Princeton University Press, 2016)
Cover -- Title -- Copyright -- Dedication -- TABLE OF CONTENTS -- List of Illustrations -- Preface -- Bibliographic Abbreviations -- Chapter 1 Introduction -- Chapter 2 The Development of the Periklean Program -- Chapter 3 The Builders of the Parthenon -- Chapter 4 The Parthenon -- Chapter 5 The Hephaisteion -- Chapter 6 The Telesterion at Eleusis -- Chapter 7 The Odeion -- Chapter 8 Temples in the Countryside -- Chapter 9 The Propylaia -- Chapter 10 Two Ionic Temples -- Chapter 11 The Periklean Legacy -- Endnotes -- Epigraphical Appendix -- Chronological Table -- Bibliography -- Subject Index -- Index Locorum.